The social identity of the Arab adolescent in the digital age: A study of the impact of interactive blogger content (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the impact of bloggers on the formation of social identity among adolescents in Arab society, focusing on the psychological and social aspects that influence adolescents' personal identity formation in light of their constant exposure to digital content The study examined how adolescents are influenced by the values and practices promoted by bloggers, such as aesthetic trends, cultural beliefs, and social concepts that may conflict with or align with the values of Arab society Theoretical models were also reviewed that explain how social media influences youth identities and how bloggers can serve as role models in building or destroying these identities The study focused on the importance of guiding adolescents toward the conscious and productive use of digital content
Keywords: Bloggers-- Social identity - Teenagers - Arab society